For safety and security reasons - Paraskevadakis, Dimitrios (Logistics and sustainable transport, 2016)
The current development trend of Internet of Things (IoT) aims for a tighter integration of mobile and stationary devices via various networks. This includes communication of vehicles to roadside infrastructure (V2I), as well as intelligent sensors / actors in Logistics and smart home environments. Compared to isolated traditional embedded systems, the exposure to open networks increases the attack surface, and errors in the networking components could compromise the safety and security of the embedded application or the whole network. But often current system architectures for mass-market IoT devices lack the required isolation concepts. Using a partitioning microkernel and enforcing the use of a microcontroller's memory protection unit (MPU) facilities, we compare different isolation concepts for a publish/subscribe middleware implementing OMG's Data Distribution Service (DDS) standard and we evaluate our results on an STM32F4 microcontroller. The results of this case study show moderate costs for increased memory usage and additional context switches.
Keywords: component-isolation; internet stvari; IoT; izolacija komponent; microkernel; mikrojadro; partitioning